Subpopulations of mononuclear leukocytes associated with inhibition of Ehrlich ascites tumor growth by treatment with Bothrops jararaca venom - Santos, MMD; da Silva, R. J.; Silva, Marcia Guimarães da [UNESP]; Fecchio, Denise [UNESP] (Carfax Publishing, 2004)
Snake venoms have been used as antineoplastic substances in several experimental models. We demonstrated in previous studies that Bothrops jararaca venom (BjV) induces inhibition of Ehrlich ascites tumor ( EAT) growth accompanied by an increase of mononuclear (MN) leukocytes in all groups inoculated with EAT and/or venom. The objective of the present study was to characterize the subpopulations of MN leukocytes involved in the inhibition of EAT growth by treatment with BjV. Swiss mice were inoculated with 1.0 x 10(3) EAT cells by the intraperitoneal route and treated with 0.4 mg/kg of BjV by the same route ( Group TV). Treatment was started 24 h after tumor cell inoculation and consisted of five intraperitoneal injections performed at 72 h intervals. After 2, 8 and 14 days, groups of animals were sacrificed and the number of B, TCD4 and TCD8 lymphocytes, macrophages and natural killer cells present in the peritoneal cavity was determined by flow cytometry. The control group consisted of animals inoculated with EAT and treated with 0.1 ml of saline under the same conditions as the experimental group ( Group T). Two additional control groups consisted of animals not inoculated with EAT and treated with saline or venom. Data were analyzed statistically by the Kruskal - Wallis nonparametric test for independent samples. on the 2nd and 8th day we observed a difference between groups T and TV ( group T > group TV) for all cell types, except natural killer cells, that only differed on the 2nd day. However, on the 14th day there was no difference in MN cells among groups. These data suggest that the inhibition of EAT is related to the toxic action of BjV on tumor cells and/or to the proteolytic effect of the venom on the mediators produced by the cells for growth modulation.
Keywords: mononuclear leukocytes; Ehrlich ascites tumor; venom; Bothrops jararaca